Waterfront regeneration in Australia: Local responses to global trends in reimagining disused city docklands. (14th April 2021) - Oakley, Susan
Abstract: This article applies ideas about critical urban assemblages to understand the planning processes, politics, and delivery of waterfront regeneration from an Australian perspective, drawing on the Port Adelaide waterfront in South Australia as a case study. Waterfront regeneration is associated with global economic deregulation, market‐led development, changes to planning regulatory requirements, and "streamlined" governance arrangements. The global spread of waterfront regeneration is an outcome of such processes, with individual waterfronts being "remade" and reimagined to reflect priorities emphasised by those forging urban policies linked to inter‐urban competitiveness and neoliberal urbanism. Waterfront developments may be categorised as "models" of success or failure that limit deeper analysis that can advance theory and practice. How such projects reflect interactions across local and global scales rather than just being expressions of global forces is a question often ignored; so, too, are those considering how policy and politics mediate those relationships. Ideas, strategies, capital, people, policy, and politics are dynamic, provisional, and contested, and are produced and assembled in particular ways to suit specific spatiotemporal contexts. On that understanding, the aim of this article is to highlight how the Port Adelaide waterfront is undergoing assembly and reassembly to reflect socioeconomic priorities and metropolitan planning agendas.